(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To share our experience with buccal mucosal graft (BMG) urethroplasty for the management of anterior urethral strictures in BIRDEM General Hospital, Dhaka. Materials and methods: This study was conducted from January 2013 to January 2018. Patients selected according to inclusion and exclusion criteria. The oral mucosal characteristics were assessed in all patients during the initial workup. Single stage dorsolateral onlay graft urethroplasty done in all patients. They were followed according schedule for outcome and complications. Result:Total 59 patients were studied. Overall success rate of BMG urethroplasty was 88.1% at 12th month. Complications include development of periurethral abscess (3.4%), restructure (8.5%) development of fistula (1.7%). Total 8 patients underwent retreatment procedures like drainage of periurethral abscess, dilatation, optical internal urethrotomy (OIU) and revision urethroplasty. Conclusion:The buccal mucosa is easy to obtain and handle, therefore BMG urethroplasty is a safe and effective in managing anterior urethral stricture. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.128-131